2018
DOI: 10.1093/jac/dky116
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for responsible antibiotic use in the inpatient setting: a systematic review followed by an international multidisciplinary consensus procedure

Abstract: BackgroundThis study was conducted as part of the Driving Reinvestment in Research and Development and Responsible Antibiotic Use (DRIVE-AB) project and aimed to develop generic quality indicators (QIs) for responsible antibiotic use in the inpatient setting.MethodsA RAND-modified Delphi method was applied. First, QIs were identified by a systematic review. A complementary search was performed on web sites of relevant organizations. Duplicates were removed and disease and patient-specific QIs were combined int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
0
52
0
Order By: Relevance
“… 10 , 16 , 17 This review is reported following the PRISMA statement. 18 This literature review was conducted alongside five other literature reviews, on responsible use of antibiotics, 19 variation in antibiotic use, 20 QIs for the inpatient setting, 21 quantity metrics for the outpatient setting 22 and quantity metrics for the inpatient setting. 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 16 , 17 This review is reported following the PRISMA statement. 18 This literature review was conducted alongside five other literature reviews, on responsible use of antibiotics, 19 variation in antibiotic use, 20 QIs for the inpatient setting, 21 quantity metrics for the outpatient setting 22 and quantity metrics for the inpatient setting. 23 …”
Section: Methodsmentioning
confidence: 99%
“…The selection process of the stakeholders is described elsewhere. 21 The complete list of stakeholders is presented in the Acknowledgements section and full details are available in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review of the literature was conducted as part of the European DRIVE-AB project and its primary objective was to describe the variation in use of antibiotics in outpatient and inpatient settings. 1 Further systematic reviews in the context of DRIVE-AB aimed to specifically assess the definition of responsible use of antibiotics 14 and to assess quantity metrics and quality indicators for antimicrobial use in the inpatient 15 , 16 and outpatient settings. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…The importance of infection prevention and control in parallel to ABS activities to limit the emergence and spread of resistant bacteria as well as reduce the use of antibiotics is largely recognized. The DRIVE-AB project developed quantity metrics and quality indicators to assess antibiotic use for both inpatient and outpatient care settings that should guide ABS activities [26][27][28][29]. In the Netherlands, since 2014, all hospitals are required by the Health Care Inspectorate and the Minister of Health to establish an antimicrobial stewardship team [30].…”
Section:  (7) Ensure Implementation Of Antibiotic Stewardship and Inmentioning
confidence: 99%